Composition containing titanium apatite and applications thereof

By using titanium aluminate as a photocatalyst, combining silicate and water and other components to form an inorganic coating, the problems of poor adsorption performance of titanium oxides and deterioration of resin molded products are solved, and the effect of efficient decomposition of organic matter and preventing surface deterioration is achieved.

JP2025014413APending Publication Date: 2025-01-30ECONOMY RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023116936
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

When existing titanium oxides are used as photocatalysts, their adsorption performance is poor, resulting in limited oxidation and decomposition of organic matter, and addition to resin molding products will cause the resin surface to gradually deteriorate and degrade.

Method used

Titanium aluminate is used as a photocatalyst, combined with components such as silicate and water to form an inorganic coating, which is applied to the surface of resin or concrete. It improves the decomposition efficiency of organic matter through physical adsorption and chemical adsorption, and prevents the deterioration of the resin surface.

Benefits of technology

It improves the decomposition efficiency of organic matter, prevents the deterioration of the resin and concrete surface, and has antibacterial, anti-fouling and deodorizing effects, while not affecting the durability of the resin and concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014413000001
    Figure 2025014413000001
  • Figure 2025014413000002
    Figure 2025014413000002
Patent Text Reader

Abstract

To provide a composition containing a photocatalyst that has photocatalytic capability along with superior adsorption properties, and does not induce chalking when added to resin.SOLUTION: A composition of the present invention contains titanium apatite as a photocatalyst with both adsorption and photocatalytic capabilities, as well as other components.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition containing titanium apatite that exhibits photocatalytic function and uses thereof. [Background technology]

[0002] Photocatalysts that can oxidatively decompose nearby organic matter by irradiation with light have been widely used in antibacterial agents, disinfectants, antifouling agents, deodorants, environmental purification agents, etc. Organic matter that can be subject to oxidative decomposition includes, for example, dust, sludge, hand oil, sebum, waste liquid, exhaust gas, microorganisms, viruses, bacteria, and other harmful substances.

[0003] In particular, titanium oxide (TiO 2 Titanium oxide is a semiconductor material, and when it absorbs light, electrons in the valence band transition to the conduction band, and this transition creates holes in the valence band. The electrons that transition to the conduction band then reduce oxygen in the air to produce superoxide anions (·O2 - ), and the holes generated in the valence band oxidize the water adsorbed on the titanium oxide surface to generate hydroxyl radicals (·OH). The hydroxyl radicals (·OH) have a very strong oxidizing power, so when the above-mentioned organic matter is adsorbed on titanium oxide, the hydroxyl radicals act to break down the organic matter into water and carbon dioxide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-349327 Summary of the Invention [Problem to be solved by the invention]

[0005] However, titanium oxide has a poor ability to adsorb organic matter onto its surface, so there was a limit to the photocatalytic (oxidative decomposition) function that could be obtained. Also, when titanium oxide was previously added as a photocatalyst to resin molded products, the resin surface gradually turned into powder and weathered, causing a problem known as chalking, which deteriorated the resin.

[0006] Therefore, the present invention has been made to eliminate the drawbacks of the above-mentioned conventional technology, and aims to provide a composition containing a photocatalyst that has photocatalytic function while also having excellent adsorption properties, and that does not cause chalking when added to resin. [Means for solving the problem]

[0007] The means for solving the problems are described below together with the reference numerals used in the description of the embodiment of the invention. The reference numerals are used to clarify the correspondence between the description of the claims and the description of the embodiment of the invention, and needless to say, are not used to restrict the interpretation of the technical scope of the present invention.

[0008] In order to achieve the above object, the composition of the present invention contains titanium apatite having adsorptive properties and photocatalytic functions, and other components (claim 1).

[0009] In addition, the composition of the present invention is preferably such that the other components are at least silica and water (claim 2), and is preferably an inorganic paint containing the composition (claim 3). In addition, in the inorganic paint, the silica is preferably colloidal silica (claim 4).

[0010] Moreover, it is preferable that the inorganic coating material contains 5 to 15 mass % of the titanium apatite in the composition and 95 to 85 mass % of the other components including silica and water (claim 5).

[0011] In addition, a painting method in which the inorganic paint is applied to concrete (Claim 6) is preferably used, and it is also preferable to form a laminated structure having a coating layer formed by the inorganic paint on the surface of the concrete (Claim 7).

[0012] Furthermore, in the above-mentioned coating method and laminated structure, it is preferable that the above-mentioned concrete contains a photocatalyst or an antibacterial agent (Claim 8, Claim 9).

[0013] Furthermore, a coating method (claim 10) is preferably used in which an inorganic zinc paint whose main components are silica, zinc and water is applied to the object to be coated, and then the inorganic paint is applied. It is also preferable to form a laminated structure on the surface of the object to be coated, having a base coating layer formed by the inorganic zinc paint, and a coating layer formed by the inorganic paint on the base coating layer (claim 11).

[0014] Furthermore, it is preferable that the inorganic zinc paint contains titanium apatite (claims 12 and 13).

[0015] It is also preferable to blast the surface of the object to be coated before applying the inorganic zinc paint (Claim 14, Claim 15).

[0016] Furthermore, in the composition of the present invention, the other component may be a resin (Claim 16), and it is preferable that the composition is molded into a resin molded product (Claim 17).

[0017] Furthermore, the other components of the composition of the present invention may be a thermoplastic resin and wood powder (Claim 18), and it is preferable that the composition is molded to form synthetic wood (Claim 19) or extruded together with a foaming agent to form a wood foamed molded body (Claim 20). Effect of the Invention

[0018] The composition of the present invention described above contains titanium apatite, which has excellent adsorption and decomposition properties, and thus significantly improves the decomposition efficiency of the organic matter. In addition, titanium apatite does not cause the chalking and does not deteriorate the resin. [Brief description of the drawings]

[0019] [Figure 1] FIG. 2 is a diagram illustrating the adhesion between an inorganic paint made of a composition of the present invention containing silica as another component and a concrete wall. [Diagram 2] FIG. 2 is a diagram illustrating the adhesion between an inorganic paint made of a composition of the present invention containing silica as another component and a concrete wall. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention is a composition containing titanium apatite as a photocatalyst.

[0021] The titanium apatite used in the present invention is a photocatalyst having a chemical structure in which part of the calcium in calcium hydroxyapatite is replaced with titanium. For example, Ca 10 (PO 4 ) 6 (OH) 2 In calcium hydroxyapatite, part of the Ca is replaced by Ti. 9 Ti(PO 4 ) 6 (OH) 2 It is expressed as:

[0022] The calcium hydroxyapatite (CaHAP) has excellent ability to adsorb the above-mentioned organic substances. The adsorption characteristics of calcium hydroxyapatite are physical adsorption (Van der Waals forces acting between molecules) and hydrophobic phosphate groups (PO 4It is believed that chemical adsorption occurs due to the hydrophilic hydroxyl group (OH) and the Ca of calcium hydroxyapatite. As described above, the titanium apatite has a crystal structure in which part of the Ca in calcium hydroxyapatite is replaced with Ti, and at the site where the Ti is introduced, a titanium oxide-like partial structure that is similar to the chemical structure of titanium oxide that exerts photocatalytic functions is formed.

[0023] As described above, since the titanium oxide-like partial structure capable of exerting a photocatalytic function is present in the crystal structure of calcium hydroxyapatite, which has excellent organic matter adsorption properties, the organic matter to be decomposed is adsorbed and the contact efficiency with the titanium oxide-like partial structure is improved. As a result, the titanium oxide-like partial structure can efficiently oxidize and decompose organic matter (e.g., dust, sludge, hand oil, sebum, waste liquid, exhaust gas, microorganisms, viruses, bacteria, and other harmful substances).

[0024] Photocatalytic apatite with the above-mentioned chemical structure exhibits a more efficient photocatalytic action (decomposition action) than titanium oxide, which has poor adsorption power, under light irradiation conditions due to the synergistic effect of its high adsorption power and photocatalytic function, and also exhibits efficient antiviral, antibacterial, antifouling and deodorizing actions, etc. In addition, in dark places, its high adsorption power allows it to strongly adsorb mold, bacteria, etc., and exhibits an antibacterial action that prevents or inhibits their proliferation.

[0025] The titanium dioxide used in the present invention is preferably in the form of particles, and has an average particle size of 0.1 to 25 μm, preferably 3 to 8 μm, but is not limited thereto.

[0026] The composition of the present invention contains, in addition to the above-mentioned titanium apatite, other components such as inorganic substances and resins.

[0027] The other components of the composition in a preferred embodiment of the present invention and suitable uses of the composition will be described below.

[0028] A preferred embodiment of the composition of the present invention is a composition containing silica (SiO2 ) and water, and the composition is used as a paint (inorganic paint). Note that, hereinafter, the composition of this embodiment is referred to as a composition for inorganic paint.

[0029] The silica is a main component (binder) in the inorganic coating composition of this embodiment. In this embodiment, colloidal silica may be used, in which silica particles are supplied in a form of colloidal dispersion in water, as described below. The average particle size of the colloidally dispersed silica particles (colloidal silica) is preferably 1 to 1000 nm. In addition, the colloidal silica is preferably porous.

[0030] When fine silica particles, such as colloidal silica, are used, the coating film of the inorganic coating containing the inorganic coating composition of this embodiment has a structure similar to that of a fine particle paving, and the coating film becomes highly hydrophilic (contact angle with water is 3 to 20 degrees). As a result, moisture in the air is adsorbed to the coating film, and a thin water film is formed on the coating film. Therefore, even if contaminants adhere to the coating surface, the moisture on the coating surface makes the contaminants easy to float up and easy to wash away with rainwater, etc. (self-cleaning effect). In addition, while organic coatings are prone to static electricity, the inorganic coating of this embodiment has high conductivity due to the thin water film formed on the coating film, so static electricity is less likely to accumulate, and the surface is less susceptible to dust and dirt.

[0031] In addition, for the inorganic paint containing the inorganic paint composition of this embodiment, for example, fine silica particles may be used to allow air to pass through the gaps between the fine particles in the coating film of the inorganic paint, thereby providing breathability to the coating film itself. Furthermore, imparting breathability to the coating film can assist the adsorption of organic matter by the titanium apatite in the coating film, thereby improving the decomposition efficiency of the organic matter.

[0032] Furthermore, in order that an inorganic paint containing the inorganic paint composition of this embodiment can more effectively exhibit its photocatalytic function after application, it is preferable that the titanium apatite is in a so-called supported state, that is, attached or fixed to the silica, which is the main component in the coating film, and that the titanium apatite is located as close to the surface layer of the coating film as possible.

[0033] The method for supporting titanium apatite on silica is not limited to the above, but for example, a method of coating the silica with titanium apatite by applying titanium apatite to the surface of the silica may be employed.

[0034] It is also preferable to support titanium apatite on fine silica particles so that the titanium apatite is disposed in the gaps formed between the fine particles after coating, or to support titanium apatite within the pores of porous silica.

[0035] As a result, the substance to be decomposed (organic matter) can be adsorbed into the voids or pores due to the adsorption capacity of the voids themselves or the adsorption capacity of the pores themselves that the porous silica possesses, and by supporting titanium apatite within the voids or pores as described above, the effect of the decomposition action (photocatalytic action) on the substance to be decomposed adsorbed within the voids or pores can be significantly increased.

[0036] In addition, silica (SiO 2 ) is translucent to near-ultraviolet rays of 350 to 400 nm, which are effective for the photocatalytic properties of titanium apatite, so photocatalytic functions can be expected from the titanium apatite inside the coating film and the titanium apatite within the pores of porous silica.

[0037] As a method for supporting titanium apatite on porous silica, for example, the silica may be coated with titanium apatite as described above.Furthermore, in a method (coprecipitation method) in which calcium nitrate, phosphoric acid, and titanium sulfate are added to water as a medium to obtain an acidic aqueous solution, to which a titanium apatite precipitant (e.g., ammonia water) is added to obtain a titanium apatite precipitate (precipitate), porous silica is added before the addition of the titanium apatite precipitant, and titanium apatite is precipitated on the porous silica, thereby making it possible to achieve a state in which titanium apatite is supported within the pores of the porous silica.

[0038] The porous silica is not particularly limited, but examples thereof include porous colloidal silica and silica (SiO 2 The diatomaceous earth, which is mainly composed of diatomaceous earth, is suitable because it is not an aggregate of fine powder but an aggregate of relatively large particles having complex pores.

[0039] In order to support the titanium apatite particles within the pores of porous silica, the particle size of the titanium apatite particles may be set to 1 μm or less.

[0040] The water used in this embodiment serves as a dispersion medium that stably disperses multiple types of paint components in the inorganic paint composition. Because water is used in this way and no volatile organic solvents (thinners, etc.) are used, the composition has almost no odor and does not have any adverse effects on people and the environment.

[0041] The inorganic coating composition of this embodiment may further contain extender pigments, inorganic pigments, inorganic fillers, organic resins, other additives, and the like, as necessary.

[0042] The extender pigment is blended for the purpose of reinforcing performance aspects such as the role of an extender and the adjustment of fluidity, strength, gloss, viscosity, and adhesion, and examples of such extender pigments include calcium carbonate, barium sulfate, aluminum hydroxide, alumina, etc. Alumina is preferable, but is not limited to this.

[0043] As the inorganic pigments, metal oxides such as iron oxides, chromium oxides, cobalt oxides, titanium dioxides, ferromanganese oxides, nickel or chromium antimony titanium oxides are preferably used, and they are prepared in various colors such as red, black, yellow, orange, brown, green, and white.

[0044] In addition, the metal oxide may be, for example, TiO 2 (titanium oxide, anatase, rutile), ZnO (zinc oxide, zinc oxide), CoO (cobalt oxide), Cr 2 O 3 (Chromium oxide), Fe 3 O 4 (Ferrite), Fe 2 O 3 Examples include single metal oxides such as FeO (ferrous oxide, ferric oxide) and CuO (copper oxide), as well as composite oxides of two to four types of metals such as (Cu·Cr) oxide, (Ti·Co) oxide, (T·Ni) oxide, (Al·Co) oxide, (Co·P) oxide, (Cr·Al) oxide, (Cr·Sn) oxide, (Fe·Mn) oxide, (Fe·Zr) oxide, (Fe·Zn) oxide, (Fe·Cr·Zn) oxide, (Fe·Co·Cr) oxide, (Co·Cr·Al) oxide, (Ti·Fe·Zn) oxide, (Cr·Cu·Mn) oxide, (Ti·Ni·Co) oxide, (Fe·Cr·Al·Zn) oxide, and (Ti·Ni·Co·Al) oxide.

[0045] The inorganic fillers are added for reasons such as improving the hardness of the coating film, preventing cracks in the coating film, and preventing paint settling, and examples of such fillers include potassium titanate, aluminum borate whiskers, alumina, silicon nitride, silicon carbide, silica-alumina whiskers, glass fibers, carbon fibers, and other fine powders, with potassium titanate being particularly preferred.

[0046] The organic resin is for strengthening the adhesive strength to the coating object, and although various organic resins can be used, it is preferable to use acrylic resin. Note that if the organic resin content (carbon content) is high, the weather resistance (for example, strength against ultraviolet rays) of the inorganic paint is lost, so it is preferable to adjust the organic resin content so that the inorganic component in the inorganic paint composition is 85 to 95%, preferably 90 to 95% (adjust the organic component to be 5 to 15%, more preferably 5 to 10%).

[0047] Examples of the other additives include dispersants, viscosity modifiers, curing catalysts, surface modifiers, defoamers, plasticizers, film-forming aids, antioxidants, etc. The types and amounts of additives to be contained can be appropriately selected depending on the purpose.

[0048] Furthermore, as a result of intensive research by the inventors into the content of the titanium apatite in the inorganic coating composition of this embodiment used in inorganic coating, it was found that the titanium apatite can be spread evenly and neatly on the surface of the coating target when coating, and that the photocatalytic function can be fully exerted even if the coating thickness is thin (for example, 1 to 10 μm), so it is preferable that the titanium apatite in the inorganic coating composition is 5 to 15 mass %, and the other components including silica and water are 95 to 85 mass %. If the titanium apatite is 5 mass % or less, the photocatalytic function is poor and the coating thickness needs to be thick, while if the titanium apatite is more than 15 mass %, the titanium apatite is not uniformly dispersed in the coating, making it difficult to spread it thinly and apply it.

[0049] Moreover, the coating thickness of the inorganic coating containing the inorganic coating composition of the present invention is preferably 1 to 100 μm, more preferably 2 to 40 μm, and further preferably 5 μm to 15 μm from the viewpoint of cost reduction.

[0050] As described above, inorganic paints containing the inorganic coating composition of the present invention can be spread thinly onto the object to be coated, so users do not need special coating techniques, and the coating thickness can be thin, so there are no costs involved.

[0051] In addition, the inorganic paint containing the inorganic paint composition of the present embodiment described above is a functional paint that can be applied to the surfaces of steel materials (infrastructure parts such as bridges and steel towers, and steel structures such as facility plants and cranes), other metals, concrete, plastics, wallpaper, wall materials, floor materials, curtains, aquaculture nets, water tanks, water intakes, water storage tanks, etc., and can impart photocatalytic properties to the objects to be coated in addition to the properties of inorganic paint. The photocatalytic properties of titanium apatite include, for example, adsorbing and reliably oxidizing and decomposing organic matter such as attached hand oils and other dirt, dust, dirt, bacteria, viruses, exhaust gases, and other harmful substances floating in the surroundings, thereby exhibiting antiviral properties, antibacterial properties, deodorizing properties, antifouling properties, etc., and preventing deterioration of the objects to be coated themselves. In addition, for objects that are constantly immersed in water or seawater, such as aquaculture nets, water tanks, water storage tanks, water intakes, etc., the decomposition action (photocatalytic function) of organic matter by titanium apatite provides anti-algae and anti-shellfish effects in addition to those described above.

[0052] The properties of the inorganic paint include, for example, heat resistance, static electricity resistance, and excellent rust prevention. Furthermore, since the inorganic paint of the present invention has zero or low carbon content (organic components), it is weather resistant (does not deteriorate due to ultraviolet rays), has a long life, and is fire resistant.

[0053] Furthermore, since the inorganic paint containing the inorganic paint composition of this embodiment has a long life as described above, once it is applied, the above-mentioned effects can be maintained for a long period of time, reducing the number of times the paint needs to be repainted, making it economical.

[0054] Furthermore, by using a coating method in which an inorganic paint containing the inorganic coating composition of the present invention is applied to concrete, the above-mentioned properties can be imparted to the concrete to which it is applied, and the layered structure in which a coating layer of the inorganic paint is formed on the surface of the concrete further enables the coating layer to exhibit strong adhesion to the concrete.

[0055] In detail, the surface of the silica contained in the inorganic coating composition of the present invention has silicon bonded to a hydroxyl group called a silanol group (Si-OH), while the surface of the concrete (substrate) is in a substrate-OH or substrate-OOH state due to moisture in the air and carbon dioxide gas, etc. (see Figure 1).

[0056] When an inorganic coating made of the inorganic coating composition of the present invention is applied, a dehydration condensation reaction occurs between the silanol groups on the silica surface, and also between the silanol groups on the silica surface and the active parts of the concrete (substrate), OH and OOH, forming a siloxane bond (Si-O-Si) and a covalent bond between the Si-O-substrate. In particular, the covalent bond between the Si-O-substrate allows the coating (coating layer) to adhere strongly to the concrete (see Figure 2).

[0057] Therefore, an inorganic paint containing the inorganic paint composition of the present invention adheres strongly to concrete (substrate), so the coating film is less likely to peel off and a beautiful painted surface can be maintained for a long period of time.

[0058] Furthermore, when applying directly to a concrete pouring surface, the main component of the paint, silica (SiO 2 ) and concrete calcium (Ca(OH) 2 ) reacts to form calcium silicate (CaSiO 3 This can form a layer that hardens the surface, leading to cost savings, especially when painting exposed concrete.

[0059] Furthermore, when concrete heats up and the internal moisture expands, in the case of organic paint, internal condensation water accumulates in the paint film and painted surface, causing the paint film to swell and peel off. However, as described above, the paint film of the inorganic paint of this embodiment, which uses fine silica particles including colloidal silica, is in a state where the fine particles are spread all over, and the tiny voids in the paint film allow the internal condensation water to be released (it has moisture breathing properties), thereby preventing the paint film from swelling and peeling off.

[0060] The above-mentioned concrete is made by mixing cement with aggregates such as sand and gravel and water, and the cement that can be used can be any of Portland cement, slag cement, silica cement, fly ash cement, blast furnace cement, alumina cement, etc.

[0061] Furthermore, the inorganic coating composition of the present invention can be applied to new and existing concrete structures and products, specifically, it can be applied to structures and equipment such as concrete bases, exposed concrete, precast concrete, extruded cement boards, GRC panels, and ceramic roofing materials.

[0062] Furthermore, if the concrete itself to be coated contains a photocatalyst (titanium apatite, titanium oxide, etc.) or an antibacterial agent, etc., and then an inorganic paint containing the inorganic paint composition of the present invention is coated on it, it is even more effective because it can exert antibacterial and antifouling effects in a superimposed manner. As described above, the inorganic paint of this embodiment can be made thin in film thickness, i.e., the light transmission distance can be shortened, so that the photocatalyst in the concrete can absorb the light that has passed through the inorganic paint film and exert its function.

[0063] Furthermore, even if for some reason light does not reach the concrete itself sufficiently, by incorporating an antibacterial metal such as silver or copper, which exhibits antibacterial properties without absorbing light, as an antibacterial agent, the inorganic paint containing the inorganic paint composition of the present invention and the antibacterial agent can exert overlapping antibacterial and antifouling effects, effectively preventing deterioration of the concrete to which it is applied.

[0064] As for the antibacterial agents that do not require light, antibacterial metals such as silver, copper, zinc, nickel, cadmium, lead, etc., and titanium phosphate-based compounds have antibacterial and antifungal properties, and in particular, zeolite, amorphous aluminosilicate, silica gel, tobermorite, or apatite carrying the antibacterial metals such as silver or copper or titanium phosphate-based compounds are preferably used.

[0065] In addition to directly applying the inorganic paint containing the inorganic paint composition of this embodiment to the object to be coated as described above, for example, an inorganic zinc paint may be applied to the object to be coated as a base paint, and then the inorganic paint of this embodiment may be applied.

[0066] The inorganic zinc paint used in the present invention is composed mainly of zinc, silica and water.

[0067] As a result, when the inorganic zinc paint is applied to steel, for example, it takes advantage of the fact that the zinc has a greater tendency to ionize and rust more easily than iron, causing the painted parts to rust instead, thereby providing an anti-rust effect (sacrificial anti-corrosion effect) that protects the iron from corrosion; on the other hand, when applied to concrete, the silica provides excellent effects such as the aforementioned adhesion to concrete, hydrophilicity, and water breathability.

[0068] In addition, the inorganic zinc paint may contain titanium apatite to exert a photocatalytic effect in a superimposed manner. As described above, the inorganic paint of this embodiment can be thinned, so that the titanium apatite in the inorganic zinc paint absorbs the light transmitted through the inorganic paint film and exerts its function.

[0069] In the present invention, the film thickness of the inorganic zinc paint can also be made thin, preferably 20 to 60 μm.

[0070] In addition, blasting the surface of the coating object before applying the inorganic zinc paint as a base coating to the coating object is preferable in terms of improving adhesion between the coating object and the coating film. Blasting is effective in improving adhesion to the coating film, and various blasting treatment devices can be used in this embodiment. For example, silica beads (powder) can be sprayed onto the coating object by blasting to deposit silica (SiO 2 ) may be diffused and penetrated to improve adhesion to the inorganic zinc paint containing silica.

[0071] Next, preferred examples of the composition (inorganic coating composition) of this embodiment will be described, but the present invention is not limited to the following examples.

[0072] <Creating inorganic paint> In Example 1, an inorganic paint was prepared by mixing an inorganic paint composition containing 10 mass % titanium apatite ("PHOTOHAP (registered trademark)" manufactured by Taihei Chemical Industry Co., Ltd.) and 90 mass % other components ("Toughmax MSA-1000G (N-90)" manufactured by Ceratec Co., Ltd.) at 2000 rpm for 1 minute using a planetary centrifugal mixer.

[0073] The breakdown of the other components (Toughmax MSA-1000G (N-90) manufactured by Ceratec Co., Ltd.) is 5 to 10 mass% silica, 25 to 30 mass% extender pigment (alumina, etc.), 1 to 5 mass% potassium titanate, 15 to 20 mass% inorganic pigment (metal oxide), 5 to 15 mass% acrylic resin, and 25 to 35 mass% water (including others).

[0074] In Example 2, an inorganic paint was prepared by mixing an inorganic paint composition containing 10 mass % titanium apatite ("PHOTOHAP (registered trademark)" manufactured by Taihei Chemical Industry Co., Ltd.) and 90 mass % other components ("Toughmax MS-92" manufactured by Ceratec Co., Ltd.) using a planetary centrifugal mixer at 2000 rpm for 1 minute.

[0075] The specific gravity of the other component ("Toughmax MS-92" manufactured by Ceratec Co., Ltd.) is 1.1 (20°C) and the viscosity is 8 seconds.

[0076] In addition, for the other components mentioned above (Toughmax MS-92 manufactured by Ceratec Co., Ltd.), the theoretical application amount for the target concrete is 80 to 160 g / m 2 (However, this depends on the amount of absorption of the concrete to which it is applied.)

[0077] In addition, when the other components (Toughmax MS-92 manufactured by Ceratec Co., Ltd.) are applied to concrete within the above theoretical application amount range, the drying time is tactile drying time of 1 hour at 5°C and 20 minutes at 20°C, hardened drying time of 4 hours at 5°C and 1 hour at 20°C, and completely hardened drying time of 30 days at 5°C and 21 days at 20°C.

[0078] In addition, when the other component ("Toughmax MS-92" manufactured by Ceratec Co., Ltd.) is applied to concrete within the above-mentioned theoretical application amount range, the film thickness can be zero (no thickness) or extremely thin (10 μm or less) because it is impregnated into the concrete.

[0079] In addition, when applying multiple coats of the above-mentioned other components (Toughmax MS-92 manufactured by Ceratec Co., Ltd.), the minimum interval between coats is 3 hours at 5°C and 1 hour at 20°C.

[0080] <Evaluation of photocatalytic activity> A primer ("Toughmax MC Primer" manufactured by Ceratec Co., Ltd.) was applied to an acrylic plate (50 mm square) with a brush in advance and dried. The inorganic paints of Examples 1 and 2 were then applied to the primer-coated acrylic plate with a brush to produce Samples 1 and 2 (film thickness: 10 μm). Then, 0.1 ml of test liquid (10 ppm methylene blue aqueous solution) was dropped onto the surface of each of Samples 1 and 2, and a covering film (50 μm thick, 30 mm square LDPE film) was placed over the surface to spread the test liquid evenly over the surface of each of Samples 1 and 2. Then, each of Samples 1 and 2 was exposed to ultraviolet light (1 mW / cm 2 ) and the decolorization state of the test solution was visually confirmed every hour.

[0081] Two hours after exposure to ultraviolet light, both Sample 1 and Sample 2 were completely decolorized, confirming the photocatalytic effect of titanium apatite.

[0082] Furthermore, Example 1 (inorganic paint) was able to more effectively exert its anti-algae and anti-shellfish effects when the objects to which it was applied were those that were constantly submerged in water or seawater, such as aquaculture nets, aquariums, water storage tanks, and water intakes.

[0083] Moreover, Example 2 (inorganic paint) could be spread more thinly onto the object to be coated.

[0084] In addition, Example 2 contains the other components mentioned above ("Toughmax MS-92" manufactured by Ceratec Co., Ltd.), and thus has excellent heat resistance, weather resistance, water resistance, and oil resistance, making it ideal for finishing the interior and exterior surfaces of buildings, concrete surfaces of civil engineering structures, and the like. Furthermore, Example 2 contains the other components mentioned above ("Toughmax MS-92" manufactured by Ceratec Co., Ltd.), which impregnate the concrete surface, increasing the hardness of the concrete surface and making it hydrophilic. As mentioned above, since the other components ("Toughmax MS-92" manufactured by Ceratec Co., Ltd.) impregnate the concrete surface, Example 2 can be applied by spreading it thinly on the concrete.

[0085] The preferred coating method for Example 2 is air spray (e.g., tip hole diameter 1 mm or less, air pressure 2 kgF / cm 2 ), a brush (the material used is preferably nylon), or a roller.

[0086] As described above, the inorganic paint of the present invention can be directly applied to a coating target such as concrete, but when using Example 2 for finishing coating of newly constructed concrete, it is preferable to thoroughly clean the surface of the concrete and oil and grease. When using Example 2 for reform coating of existing exposed concrete, it is preferable to clean off as much dirt as possible, such as soot, dust, and mold, with high-pressure cleaning water or aqueous sandblasting, and then apply Example 2 after drying.

[0087] Furthermore, the painting conditions of Example 2 are preferably used except in cases where the temperature is below 5°C, the surface temperature is above 50°C, the humidity is above 85%, or there is a risk of rainfall within 3 hours after painting outdoors (in summer).

[0088] Next, another preferred embodiment of the composition of the present invention is one that contains at least a resin as the other component in addition to titanium apatite, and uses the composition as a raw material for a resin molded product. Note that, hereinafter, the composition of this embodiment is referred to as a composition for a resin molded product.

[0089] Titanium oxide, which was previously added to resin molded products as a photocatalyst, caused the resin surface to gradually turn into powder and weather, a phenomenon known as chalking, which deteriorated the resin. Titanium apatite is advantageous in that it does not cause chalking.

[0090] The resin used in this embodiment is not particularly limited and can be appropriately selected depending on the purpose. Suitable examples include synthetic resins and biodegradable resins.

[0091] Examples of the synthetic resin include thermoplastic resins and thermosetting resins. Specific examples of these include polyolefin resins, polyester resins, polycarbonate (PC) resins, styrene resins, fluorine resins, melamine resins, alkyd resins, amino resins, epoxy resins, urethane resins, acrylic resins, vinyl chloride resins, silicone resins, phenolic resins, xylene resins, toluene resins, styrene-butadiene resins, acrylonitrile-butadiene resins, acrylonitrile-butadiene-styrene (ABS) resins, polypropylene (PP) resins, methyl methacrylate-butadiene resins, modified methyl methacrylate-butadiene resins, ethylene vinyl acetate resins, vinylidene chloride resins, etc. Among these, polyethylene, polypropylene, nylon, polyethylene terephthalate, polystyrene, polycarbonate, etc. are preferred.

[0092] The biodegradable resin may be a biodegradable resin derived from a natural product, a chemically synthesized biodegradable resin, or the like. These may be used alone or in combination of two or more kinds.

[0093] Examples of the biodegradable resins derived from natural products include chitin, chitosan, alginic acid, gluten, collagen, polyamino acids, bacterial cellulose, pullulan, curdlan, polysaccharide by-products, starch, modified starch, and microbially produced polyesters (biopolyesters).

[0094] Examples of the chemically synthesized biodegradable resin include aliphatic polyester, aliphatic / aromatic polyester, polyvinyl alcohol (PVA), polyurethane (PU), and the like.

[0095] To explain the method of producing a resin molded product from the composition containing titanium apatite and resin of this embodiment (composition for resin molded products), for example, the composition for resin molded products is kneaded with a kneader to uniformly mix the titanium apatite and polyethylene. The kneaded product is then cooled and cut into pellets. Next, the pellets are molded into a predetermined shape using an injection molding machine to produce a resin molded product. Note that the composition for resin molded products of this embodiment may be used as it is as a molding material without being formed into pellets as described above.

[0096] Furthermore, the composition for resin molded products of this embodiment may further contain fillers such as talc, pigments, flame retardants, plasticizers, reinforcing agents, etc., as necessary.

[0097] The resin molded products obtained from the composition for resin molded products of this embodiment can, due to the photocatalytic function of titanium apatite, adsorb and reliably oxidize and decompose, for example, attached hand oils and other dirt, as well as organic matter such as dust, dirt, bacteria, viruses, exhaust gases, and other harmful substances floating in the surrounding area, thereby exhibiting anti-fouling, antibacterial, anti-viral, deodorizing properties, etc., and preventing deterioration of the molded product itself.

[0098] As for the content of the titanium apatite in the composition for resin molded products of this embodiment, the inventors have carefully studied the content of the titanium apatite, and have found that in order for the titanium apatite to remain uniformly dispersed within the resin molded product without agglomeration, for the titanium apatite not to fall off from the resin molded product, and for the titanium apatite to effectively exert its photocatalytic function, it is preferable for the titanium apatite in the composition for resin molded products to be 1 to 15 mass%, preferably 1 to 10 mass%, and for the other components including resin to be 99 to 85 mass%.

[0099] The uses of the resin molded products produced from the composition for resin molded products of the present invention are not particularly limited, but they can be used in a variety of common products such as automobiles, building materials, home appliances, stationery, and other daily necessities, and their shape is also not particularly limited, and they can be, for example, in sheet form.

[0100] Furthermore, another preferred embodiment of the composition of the present invention contains, in addition to titanium apatite, as the other components, thermoplastic resin and wood flour, and uses the composition as a raw material for synthetic wood. Hereinafter, the composition of this embodiment will be referred to as a composition for synthetic wood.

[0101] Generally, synthetic wood obtained by melting and kneading thermoplastic resin and wood powder together and molding the resulting molded material into a desired shape has the texture of wood while also possessing the properties of a resin molded body, such as resistance to decay, and is therefore widely used, for example, as building materials for wood decks installed outdoors and as sheathing for concrete formwork. The synthetic wood obtained from the synthetic wood composition of this embodiment contains titanium apatite, which has a photocatalytic effect that adsorbs and reliably oxidizes and decomposes attached hand oils and other dirt, as well as organic matter such as dust, dirt, bacteria, viruses, exhaust gases, and other harmful substances floating in the vicinity, thereby providing anti-fouling, antibacterial, anti-viral, and deodorizing effects, and effectively preventing deterioration of the synthetic wood itself.

[0102] As the thermoplastic resin used in this embodiment, various types of thermoplastic resins can be used, but preferably polyolefin resins such as polypropylene (PP) and polyethylene (PE), and resins having polyolefin resins as their main component (hereinafter, polyolefin resins and resins having polyolefin resins as their main component are collectively referred to as "polyolefin-based resins").

[0103] Furthermore, these thermoplastic resins may be used alone or in combination with several different types. For example, it is possible to use recycled plastics that contain several different types of thermoplastic resins as raw materials.

[0104] The types of polypropylene (PP) include homopolymer, random copolymer, and block copolymer, and any of these polypropylenes can be used in the present invention. In addition, any of the polypropylenes, such as polypropylene recovered in accordance with the Container Recycling Law (the so-called "Container Recycling Law"), or a mixture of various polypropylenes, can also be used.

[0105] In addition, types of polyethylene (PE) include low-density polyethylene (PE-LD), high-density polyethylene (PE-HD), and linear low-density polyethylene (PE-LLD), and all of these polyethylenes can be used.

[0106] In addition, the wood flour used in this embodiment may be obtained from various types of wood flour generally available on the market, or may be obtained by crushing waste materials such as unused wood, used construction waste, and sawdust generated during wood processing using a crusher, cutter, or mill.

[0107] The type of wood is not particularly limited, and there is no structural problem if multiple types of wood are mixed together, but taking into consideration the final finish of the wood molding, it is preferable to use wood with a relatively uniform color.

[0108] Any type of wood flour can be used as long as it has a particle size of 1,000 μm or less, and preferably has a particle size of 150 to 200 μm.

[0109] Furthermore, the wood flour may be fibrous. When the wood flour is fibrous, it is preferable that the average fiber length is 80 to 800 μm.

[0110] The wood flour used in this embodiment is preferably dried before mixing with other raw materials in order to improve compatibility with the thermoplastic resin and to prevent the generation of water vapor during heating and kneading, and it is preferable to use wood flour that has been dried to a moisture content of 1% by mass or less.

[0111] Furthermore, as a result of careful investigation by the inventors into the content of the titanium apatite in the synthetic wood composition of this embodiment, it has been found that in order for the titanium apatite to remain uniformly dispersed within the synthetic wood without agglomeration, for the titanium apatite not to precipitate from the surface of the synthetic wood, and for the photocatalytic function to be effectively exerted, it is preferable for the titanium apatite in the synthetic wood composition to be 1 to 20 mass %, and for the other components including the thermoplastic resin and wood flour to be 99 to 80 mass %.

[0112] A preferred compounding ratio of the above-mentioned wood flour to the thermoplastic resin is 30-70% by mass / 70-30% by mass, wood flour / thermoplastic resin.

[0113] In addition, the synthetic wood composition of the present invention may contain, in addition to the above-mentioned wood powder and thermoplastic resin, fillers such as talc, coloring pigments, reinforcing agents, flame retardants, paraffin wax, etc., as necessary.

[0114] The synthetic wood composition of the present invention described above can be used to mold various types of synthetic wood, and may be used as a molding material as is, but it is preferable to previously mix, knead, etc., the synthetic wood composition to form it into pellets of a specified particle size.

[0115] Such pellets can be produced using various known pellet production devices, and the production method is not particularly limited as long as pellets can be produced. For example, the raw materials can be fed together into an extruder and melt-kneaded while extruding a round, cord-like strand from a nozzle-shaped die attached to the end of the barrel of the extruder, and this strand can be cut into predetermined lengths to obtain composite pellets. Alternatively, pellets can be obtained in a batch manner by crushing pre-kneaded kneaded material using a known Henschel mixer or the like to obtain pellets in a predetermined particle size. Furthermore, composite pellets can be obtained by granulating the pre-kneaded kneaded material to a predetermined particle size by stirring before it hardens.

[0116] As for molding, various known methods such as injection molding, extrusion molding, and compression molding can be used. For example, when the synthetic wood is a long molded product such as a deck board, the long synthetic wood is extruded in a continuous longitudinal direction by extrusion molding.

[0117] Furthermore, the synthetic wood composition described above may be extruded together with a foaming agent (hereinafter, also referred to as extrusion foam molding) to produce a wood foamed article.

[0118] In addition, when extrusion foam molding is performed, the inventors have carefully considered the content of the titanium apatite in the synthetic wood composition of this embodiment and found that, in order for the titanium apatite to remain uniformly dispersed without agglomeration within the wood foam molding, for the titanium apatite not to precipitate from the surface of the wood foam molding, and for the photocatalytic function to be effectively exerted, it is preferable for the titanium apatite in the synthetic wood composition to be 1 to 20 mass %, and for the other components including the thermoplastic resin and wood flour to be 99 to 80 mass %.

[0119] A preferred compounding ratio of the above-mentioned wood flour to the thermoplastic resin is 30-70% by mass / 70-30% by mass, wood flour / thermoplastic resin.

[0120] Furthermore, with regard to the amounts of wood flour and the thermoplastic resin, for example, since foaming by the foaming agent occurs in the thermoplastic resin portion, the foaming rate can be increased by reducing the amount of wood flour and increasing the amount of thermoplastic resin; if the amount of thermoplastic resin is less than 46% by mass and the amount of wood flour is more than 35% by mass in 100% by mass of the synthetic wood composition (total molding material), the specific gravity of the resulting wood foamed molding cannot be made 0.8 or less.

[0121] On the other hand, if the amount of wood flour is reduced, the strength of the resulting wood foam molding will decrease; for example, when the wood foam molding is used as a concrete formwork board, etc., the required rigidity cannot be maintained. Therefore, it is preferable that the upper limit of the amount of thermoplastic resin to be added is 52 mass% and the lower limit of the amount of wood flour to be added is 33 mass% in 100 mass% of the synthetic wood composition (total molding material).

[0122] Furthermore, when the obtained wood foam molding is used as a concrete formwork sheathing, etc., by adding 33 to 35 mass% wood powder and adding 48 mass% or more thermoplastic resin to 100 mass% of the synthetic wood composition (total molding material), the specific gravity of the concrete formwork sheathing can be reduced to 0.75 or less.Furthermore, by approaching the upper limit of 52 mass%, the specific gravity of the concrete formwork sheathing can be reduced to 0.72.

[0123] To summarize the above, when the obtained wood foam molding is used as a concrete formwork board, etc., the preferred ratio of wood flour and the thermoplastic resin is 46 to 52 mass% thermoplastic resin and 33 to 35 mass% wood flour, relative to 100 mass% of the synthetic wood composition (total molding material).

[0124] As auxiliary materials that are added together with the above-mentioned thermoplastic resin and wood flour as a synthetic wood composition (molding material) and pelletized, talc, pigments, reinforcing agents, lubricants, etc. can be added.

[0125] For example, when the obtained wood foam molding is used as a concrete formwork board, the amount of talc added is preferably 5.7 to 10.8 mass% of 100 mass% of the synthetic wood composition (molding material), and the amount of other auxiliary materials (pigments, reinforcing agents, lubricants, etc.) added is preferably mixed in such a way that the total amount of the additives is 2.6 to 5.9 mass% of 100 mass% of the synthetic wood composition.

[0126] In the case of extrusion foam molding, an alkane may be added to the synthetic wood composition of this embodiment. The addition of an alkane promotes the mixing and dissolution of the foaming gas into the thermoplastic resin during melt kneading of the mixed material in the barrel of the extruder, while suppressing the uptake of the foaming gas into the wood powder, allowing the foaming gas to be uniformly dispersed in the molding material.

[0127] Furthermore, the addition of an alkane reduces the contact resistance between the metal surface and the molding dough, allowing the molding dough with the foaming gas uniformly dispersed therein to move smoothly, making it possible to introduce the molding dough into the molding die while maintaining the foaming gas uniformly dispersed therein.

[0128] Furthermore, by adding an alkane to the synthetic wood composition of this embodiment, the foaming gas trapped in the thermoplastic resin can be prevented from starting to expand until the pressure on the molding dough is released, and the molding dough can be prevented from starting to foam in advance before it is introduced into the molding die.

[0129] As a result, by extrusion foam molding using the synthetic wood composition (molding material) of this embodiment containing alkanes, it is possible to obtain a high-quality wood foam molded product with uniform internal bubble generation, while also improving productivity during extrusion molding.

[0130] Furthermore, when the synthetic wood composition (molding material) of this embodiment containing alkanes is a pellet obtained by melt-kneading each component so that it is uniformly dispersed, and then granulating it to a specified particle size, the molding material becomes easy to handle and pollution of the working environment can be reduced compared to when each component, including powder, etc., is handled individually.

[0131] In addition, since each of the constituent components, except for the foaming agent, is melt-kneaded in advance to a uniformly dispersed state, it becomes easier to obtain a uniform melt-kneaded state without bias among the components when melt-kneading in the extruder.

[0132] The alkane (Cn H 2n+2 ) can be used as long as it has a molecular weight of 300 to 1000 g / mol. Alkanes with a molecular weight of less than 300 g / mol have low melting and boiling points and are difficult to handle, while alkanes with a molecular weight of more than 1000 g / mol do not provide the desired effect. In other words, below the lower limit of 300 g / mol, the alkanes become closer to a fluid and have a low boiling point (below 50°C), while above 300 g / mol they become petroleum wax (solid). When they become a fluid, their dispersibility in resins (such as PP and PE) decreases, and they precipitate on the surface, preventing the desired effect from being obtained.

[0133] The preferred molecular weight range of the alkane to be added is 350 to 800 g / mol, and more preferably 400 to 600 g / mol.

[0134] The amount of alkane added is 1 to 5% by mass of 100% by mass of the synthetic wood composition (total molding material). If it is less than 1% by mass, the desired effect cannot be obtained, and if it is more than 5% by mass, the alkane will rise to the surface and the expansion ratio will decrease.

[0135] In addition, when performing extrusion foam molding, the synthetic wood composition of this embodiment is preferably first melt-kneaded while heating so that each component is uniformly dispersed to form a mixed material, which is then granulated to a predetermined particle size to produce pellets, and a foaming agent described below and, if necessary, glass fiber and / or carbon fiber are added to these pellets to produce a wood foam molded body.

[0136] In addition, the foaming agent for foaming the synthetic wood composition of this embodiment is a volatile foaming agent (gas type), CO 2 ,N 2 There are decomposable blowing agents such as fluorocarbons and propane, but any of these blowing agents may be used, and various commercially available blowing agents can be used.

[0137] In this embodiment, it is preferable to use a decomposable foaming agent. Examples of decomposable foaming agents include inorganic compounds, azo compounds, sulfonyl hydrazide compounds, nitroso compounds, azide compounds, etc. Any foaming agent may be used as long as it is easily dispersed or dissolved in polyethylene, which is the main raw material of the synthetic wood composition, and does not impart unwanted coloring to the resulting wood foamed product.

[0138] These foaming agents are commercially available in the form of pellets called "master batches" in which the foaming agent is added at high concentrations to the carrier resin, and such master batches may be used. For example, a master batch in which the carrier resin is polyethylene and the foaming agent is sodium bicarbonate, which belongs to the inorganic compound group, ["EE405F" manufactured by Eiwa Kasei Kogyo Co., Ltd.] may be used.

[0139] The foaming agent is added in a required amount depending on the gas generation rate of the foaming agent used, the foaming degree of the wood foamed molded product to be produced, etc. As an example, the amount of foaming agent (master batch) added in this embodiment is 0.3 mass % or more, preferably 0.3 to 4.0 mass %, relative to 100 mass % of the synthetic wood composition (molding material).

[0140] If necessary, glass fibers and / or carbon fibers may be added together with the foaming agent.

[0141] The glass fibers and / or carbon fibers are added to improve the strength of the resulting wood foam molding, and the added glass fibers and / or carbon fibers are preferably 20 mm or less in length, and in this embodiment, 10 mm fibers can be used.

[0142] In addition, the amount of glass fiber and / or carbon fiber added is 8 to 12 mass% relative to 100 mass% of the synthetic wood composition (molding material), and the glass fiber and / or carbon fiber are added during extrusion molding together with the foaming agent, without being pelletized together with the thermoplastic resin or wood flour.

[0143] As the carbon fiber, either PAN-based or pitch-based carbon fiber may be used. As an example, an example of the PAN-based carbon fiber is "Torayca" manufactured by Toray Industries, and as an example of the pitch-based carbon fiber is "Kureca" manufactured by Kureha Corporation.

[0144] The carbon fibers may be added as chopped carbon fibers prepared by cutting carbon yarns to the aforementioned length, or may be bundled using various sizing agents.Furthermore, carbon fibers obtained by collecting and crushing scraps generated during the manufacture of various carbon fiber products, or discarded carbon fiber products used as automobile parts, aircraft parts, etc. may also be added.

[0145] The synthetic wood composition (molding material) of this embodiment described above, the foaming agent, and glass fibers and / or carbon fibers added as necessary are continuously introduced into a screw-type extruder installed in an extrusion molding device, where they are melt-kneaded while being heated, and the molded material extruded by this extruder is introduced into an extrusion die, and then introduced into a molding die subsequent to this extrusion die, where it is molded into a predetermined shape and then cooled and solidified, thereby obtaining a wood foam molded product of the desired shape.

[0146] As the extrusion molding device used in the production of wood foam molded bodies, various types of device can be used.

Claims

1. A composition containing titanium apatite having adsorptive and photocatalytic functions and other components.

2. 2. The composition of claim 1, wherein said other components are at least silica and water.

3. An inorganic coating comprising the composition of claim 2.

4. 4. The inorganic coating material according to claim 3, wherein the silica is colloidal silica.

5. 4. The inorganic coating material according to claim 3, wherein the content of said titanium apatite is 5 to 15 mass %, and the content of said other components is 95 to 85 mass %.

6. A coating method comprising applying the inorganic coating material according to any one of claims 3 to 5 to concrete.

7. A laminated structure having a coating layer formed on a surface of concrete using the inorganic coating material according to any one of claims 3 to 5.

8. 7. The coating method according to claim 6, wherein the concrete contains a photocatalyst or an antibacterial agent.

9. 8. The laminated structure of claim 7, wherein the concrete contains a photocatalyst or an antibacterial agent.

10. A coating method comprising coating an inorganic zinc coating material containing silica, zinc and water as main components on an object to be coated, and then coating the inorganic coating material according to any one of claims 3 to 5.

11. A laminated structure having a base coating layer formed on a surface of an object to be coated with an inorganic zinc paint mainly composed of silica, zinc and water, and a coating layer formed on the base coating layer with the inorganic paint according to any one of claims 3 to 5.

12. 11. The coating method according to claim 10, wherein the inorganic zinc paint contains titanium apatite.

13. 12. The laminate structure of claim 11, wherein the inorganic zinc paint contains titanium apatite.

14. 11. The coating method according to claim 10, further comprising the step of blasting the surface of the object to be coated before coating the inorganic zinc paint.

15. 13. The coating method according to claim 12, further comprising the step of blasting the surface of the object to be coated before coating the inorganic zinc paint.

16. The composition according to claim 1, wherein said other component is at least a resin.

17. A resin molded product obtained by molding the composition according to claim 16.

18. The composition according to claim 1, wherein said other components are at least a thermoplastic resin and wood flour.

19. 20. A synthetic wood molded from the composition of claim 18.

20. A wood foamed article obtained by extruding the composition according to claim 18 together with a foaming agent.

Citation Information

Patent Citations

  • Titanium oxide panel and interior

    JP1999349327A